2018
DOI: 10.1016/j.pacs.2018.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Applying dynamic contrast enhanced MSOT imaging to intratumoral pharmacokinetic modeling

Abstract: Examining the dynamics of an agent in the tumor microenvironment can offer critical insights to the influx rate and accumulation of the agent. Intratumoral kinetic characterization in the in vivo setting can further elicudate distribution patterns and tumor microenvironment.Dynamic contrast-enhanced Multispectral Optoacoustic Tomographic imaging (DCE-MSOT) acquires serial MSOT images with the administration of an exogenous contrast agent over time. We tracked the dynamics of a tumor-targeted contrast agent, Hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…Raw data obtained with MSOT were reconstructed with multispectral analysis performed as described [35,46,61]. Spectral analysis was performed at wavelengths corresponding to the IR780, oxy-and deoxy-hemoglobin.…”
Section: Multispectral Optoacoustic Tomography Image Reconstruction Amentioning
confidence: 99%
“…Raw data obtained with MSOT were reconstructed with multispectral analysis performed as described [35,46,61]. Spectral analysis was performed at wavelengths corresponding to the IR780, oxy-and deoxy-hemoglobin.…”
Section: Multispectral Optoacoustic Tomography Image Reconstruction Amentioning
confidence: 99%
“…Aortic slices were required to measure the blood retention time for V7-TROS and TROS (Figure S5). Images were acquired analogously to the tumor, liver, kidney, and spleen, as a single snapshot kinetically at 0, 4, 8, and 24 h. , Multiwavelength illumination between 680 and 900 nm was utilized for spectral enrichment. A 10 μs acquisition time and 25 acquisitions per wavelength were used for image capture.…”
Section: Methodsmentioning
confidence: 99%
“…To date, a number of new biomedical applications have been achieved by using MCAs. [30][31][32][33][34][35] Pharmacokinetics is an important parameter used to study the movement of foreign substances (mostly the drugs) into, through and out of the organism, which includes the processes of liberation, absorption, distribution, metabolization and excretion. Recently, Xiao et al utilized MSOT to investigate the pharmacokinetics of HypoxiSense 680 (HS680), a commercially available and tumor-targeted MCA, in a mouse xenograft model of breast cancer (Fig.…”
Section: Molecular Contrast Agents (Mcas)mentioning
confidence: 99%
“…3b). 30 In addition, Lavaud et al used a new MCA (Angiostamp800) with tumor-targeting specificity, to noninvasively monitor liver metastasis progression in vivo. 31 They demonstrated that, the more advanced the metastasis development was, the higher the optoacoustic signal generated, suggesting that this strategy may be used for precisely discriminating the disease stages and the healthy state in mice.…”
Section: Molecular Contrast Agents (Mcas)mentioning
confidence: 99%